PENGARUH ROA DAN FDR TERHADAP TINGKAT BAGI HASIL DEPOSITO MUDHARABAH - Nasution, Iqbal Fadil Apriliando; Mubarokah, Isro'iyatul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.06.TAHUN.2021, 2021)
The establishment of a financial institution such as a bank in human civilization is very beneficial for humans themselves because this institution acts as a place to conduct financial transactions or as a liaison in these transactions. The research conducted intends to analyze and also explain the effect of ROA and FDR on the Profit-Sharing Rate of Mudharabah Deposits on ICB (Islamic Commercial Banks) in Indonesia in 2017-2019. The method used by researchers is a quantitative method with descriptive and verification approaches. Researchers used secondary data in this study with data sources obtained from BUS financial reports published on the official website of each bank. Researchers get a research population of 14 banks with Islamic principles and then selected samples by researchers as many as 6 Islamic banks through the purposive sampling method. The method of analyzing research data is using multiple linear regression analysis methods. From the test results in this study, it can be concluded that (1) ROA has a partial and negative correlation with the Mudharabah Deposit Profit-Sharing Rate, (2) FDR has a partial and negative correlation with the Mudharabah Deposit Profit-Sharing Rate, (3) Second ROA and FDR variables have a simultaneous effect on the Mudharabah Deposit Profit-Sharing Rate.